Gold dust woman : a biography of Stevie Nicks - Davis, Stephen, 1947- (New York : St. Martin's Press, 2017)
An in-depth portrait of the classic-rock artist covers her role in the stardom of Fleetwood Mac, the affairs that inspired her greatest songs, her struggles with addiction, and her successful solo career.--
Includes bibliographical references and index.
Keywords: Nicks, Stevie; Fleetwood Mac (Musical group); Singers -- United States -- Biography; Rock musicians -- United States -- Biography